The impact of COVID-19 pandemic on medicine security in Africa: Nigeria as a case study (2020)
COVID-19 is an unprecedented pandemic posing major threat to global public health. In the past decades of years or so, one could have heard of how dangerous it is to be virtually reliant on medicine supply from other countries. Nonetheless, no action was taken because it seemed to many that the global trade system was operational and Nigerians as well as citizens of African countries appear to have sufficient supply of the medications required at quite appealing cost. Currently in 2020, this apprehension has revolved from an imaginary problem to an actual challenge that might have consequences for millions nationwide due to COVID-19 pandemic. Now, African countries can realize that putting all our eggs in one basket was not such a good idea. In Nigeria, over 70% of the prescribed medications are produced from active ingredients (API) primarily sourced from firms in China and India. Access to medicine is an integral part of healthcare systems, uninterrupted access to medicine is much needed and essential for the well-being of the population. We are now approaching the conclusion that it is more reasonable to probably invest a little more to resuscitate a domestic pharmaceutical synthesis and herbal medicine research capacity in Nigeria and across African countries to improve public health.